2020
DOI: 10.1038/s41419-020-03267-2
|View full text |Cite
|
Sign up to set email alerts
|

PSTPIP2 inhibits cisplatin-induced acute kidney injury by suppressing apoptosis of renal tubular epithelial cells

Abstract: Cisplatin (CP) is an effective chemotherapeutic agent widely used in the treatment of various solid tumours. However, CP nephrotoxicity is an important limitation for CP use; currently, there is no method to ameliorate cisplatin-induced acute kidney injury (AKI). Recently, we identified a specific role of proline–serine–threonine phosphatase-interacting protein 2 (PSTPIP2) in cisplatin-induced AKI. PSTPIP2 was reported to play an important role in a variety of diseases. However, the functions of PSTPIP2 in exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 36 publications
(40 reference statements)
1
19
0
Order By: Relevance
“…In AKI induced by I/R, a metabolic reprogramming also has been reported with a glycolytic shift and PDC inhibition [ 29 ], indicating a decreased activity of this enzyme complex and ergo a reduction in acetyl-CoA synthesis; moreover, in AKI induced by cisplatin, H3K27 acetylation is reduced, and the restoration of its acetylation levels decreases kidney damage [ 30 , 31 ]. Hence, in CKD and AKI, there appears to be a decrease in acetyl-CoA levels, which in turn impacts histone acetylation.…”
Section: Acetyl-coamentioning
confidence: 99%
“…In AKI induced by I/R, a metabolic reprogramming also has been reported with a glycolytic shift and PDC inhibition [ 29 ], indicating a decreased activity of this enzyme complex and ergo a reduction in acetyl-CoA synthesis; moreover, in AKI induced by cisplatin, H3K27 acetylation is reduced, and the restoration of its acetylation levels decreases kidney damage [ 30 , 31 ]. Hence, in CKD and AKI, there appears to be a decrease in acetyl-CoA levels, which in turn impacts histone acetylation.…”
Section: Acetyl-coamentioning
confidence: 99%
“…Cisplatin-induced nephrotoxicity is accompanied by apoptosis of renal tubular epithelial cells, and suppression of renal tubular epithelial cell apoptosis reduces nephrotoxicity [12]. A previous study showed that ruscogenin represses lipopolysaccharide-induced apoptosis of pulmonary endothelial cells [8].…”
Section: Discussionmentioning
confidence: 98%
“…Induction of Nrf2 signalling pathway was also observed in common carp (Kövesi et al 2020b ). The experiment conducted on human hepatocytes L02 cells revealed that caveolin-1 (CAV-1) interacts with Nrf2 in response to oxidative stress caused by AFB1 to trigger apoptosis in cells (Xu et al 2020 ). A decrease in Nrf2 and HO-1 expression was also noticed in Wistar rats exposed to AFB1 and interestingly that effect was partially restored by administration of antidiabetic drug Sitagliptin (Ji et al 2020 ).…”
Section: Mycotoxinsmentioning
confidence: 99%